ANALYSIS OF FACTORS INFLUENCING MEDICINE PURCHASE DECISIONS IN CILEGON - Sofyan Ahmad, Yayan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the impact of four key marketing variables product quality, price, persuasive communication, and incentives on brand image and purchasing decisions among medical practitioners in Cilegon, Indonesia. Drawing on a sample of 225 physicians, dentists, and pharmacists, data were collected via an online Likert‐scale questionnaire and analyzed using confirmatory factor analysis and structural equation modeling (SEM). Results indicate that product quality and incentives exert statistically significant positive effects on brand image (β = 0.284, p = 0.011; β = 0.291, p = 0.003, respectively), while price and persuasive communication do not achieve significance. Furthermore, incentives also demonstrate a significant positive influence on purchase decisions (β = 0.206, p = 0.047), whereas other independent variables, including brand image, fail to show a direct effect. Model fit indices (CMIN/DF = 1.122; GFI = 0.90; RMSEA = 0.016; p = 0.061) confirm an overall good fit. These findings underscore the critical role of maintaining high product standards and ethical incentive programs in strengthening brand perception and stimulating purchase behavior in a competitive pharmaceutical landscape. Theoretical contributions include the integration of marketing, consumer behavior, and brand management theories within a single SEM framework. Practically, pharmaceutical firms operating in emerging markets should prioritize consistent quality assurance and transparent incentive mechanisms to enhance both brand equity and sales performance.